PELAYANAN KUNJUNGAN KE PANTI REHABILITASI ORANG DENGAN GANGGUAN JIWA (ODGJ) â€œRUMAH PEMULIHAN ECCLESIAâ€ DI BANTEN - Djikoren, Livia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Kristen Wira Wacana Sumba, 2023)
The issue about people with mental disorders (ODGJ) has been an unsolved problem globally and nationally. To date, there are many ODGJs that have not received a proper treatment due to the scarcity of mental hospitals and the less of mental professionals. Banten is one of the provinces that still do not have a mental hospital. Therefore, rehabilitation institution for ODGJ has been an alternative that is needed there right now. The handling of ODGJ demands a serious attention from all parties including church as a religious institution. The author together with the team from the church do a visitation to Rumah Pemulihan Ecclesia that is located at Banten as a form of churchâ€™s concern towards ODGJs. The method used in this research is an onsite accompaniment so that there is a direct interaction with those ODGJs. The activity of this visitation received a positive response and they were entertained with our ministry.